Relationship Between Vitamin D and Rheumatoid Arthritis Disease - Azzeh, Firas Sultan (Pakistan Journal of Nutrition, 2012)
Rheumatoid arthritis is a chronic inflammatory disease in which the synovial membrane of the joint becomes inflamed, resulting in a swelling, stiffness, pain, limited range of motion, joint deformity and disability. Vitamin D is the “sunshine vitamin” which is converted in the body to a hormone 1, 25- dihydroxyvitamin D3 by the photolytic action of ultraviolet light on the skin. Vitamin D plays an important role, along with the essential minerals calcium and phosphorus, in the maintenance of healthy bones and teeth. An inverse association between vitamin D intake and rheumatoid arthritis was found in some prospective studies. Although vitamin D has been implicated in a decreased risk of autoimmune diseases such as type 1 diabetes and multiple sclerosis, its role in decreasing the risk of rheumatoid arthritis remains equivocal. This scientific review is written to illustrate the possible relationships between rheumatoid arthritis and vitamin D.